The effectiveness of glass eel stocking in the Vistula Lagoon, Poland - I. Psuty; B. Draganik (Acta Ichthyologica et Piscatoria, 2008)
Background. Eel recruitment and catches have decreased drastically throughout Europe since the beginning of the 1960s (recruitment) and the 1980s (catches). Until the end of the 1990s, European eel, Anguilla anguilla, the highest priced fish, was the basis of the fishery in the Polish part of the Vistula Lagoon. The lagoon was stocked with glass eel from 1970 to 1994 with the aim of enhancing the stock of this species. Due to political and economical changes after 1989, national stocking funds were stopped. The aim of the presently reported study was to estimate the effectiveness of stocking glass eel in the Vistula Lagoon, with regard to the limited reliability of official landings data. Materials and methods. Eel catches in the Polish part of the Vistula Lagoon were reconstructed from landings statistics. Corrections of Polish landings were only based on grey literature request; political and socio-economical changes were explained in personal reviews with fishermen and fishery inspectors. The effectiveness of the stocking was estimated with the simplified method of calculating the accumulated biomass of fish from stocking with the assumed, constant coefficients F and M (fishery and natural mortality, respectively). The sensitivity analysis of F and M was estimated using the input of different parameters. Results. Changes in human history resulted in different biases in official landings statistics. The change in fishermen cooperative organisation and the martial law in Poland, during the period of 1981–1984, resulted in significant changes of the eel official landings. The reconstructed catches in this period (1980–1985) do not exceed 30% of the total exploitable biomass of the reserve for silver eel escapement, even under intensive exploitation. With assumed M and F, the exploitable stock biomass increased sharply to the peak value during the 10 years of stocking. Uncertainty concerning M for the first year of stocked eel results in a difference in the estimated biomass as high as 700 t. Conclusion. Under great uncertainties and lack of “hard data”, social science methodologies could help to estimate basic parameters for assessment models. Glass eel stocking at the Vistula Lagoon was effective both for the enhancement of the eel population and maintenance of an intensive eel fishery.